Strategic forecasting in uncertain environments: hypersonic cruise vehicle research and development case study. (January 2015) - Chudoba, B.; Haney, E.; Gonzalez, L.; Omoragbon, A.; Oza, A.
Abstract: The exponentially increasing amount of information accumulated from past to current engineering projects has created an environment where repurposing existing data to support new projects is paramount to sustainable success. Strategic planning and early design decisions, specifically, occur in decision-making environments that require information support capabilities that lie outside of traditional engineering analyses. In order to advance towards a more complete planning environment, a pragmatic methodology has been developed for modern aerospace data and information collection, categorisation, and utilisation with a focus on current efforts in hypersonic vehicle research and development. The main thrust has been to provide insights into financial and technical trends that support objective programmatic and planning decision-making. The end-product is a suite of graphical decision-making interfaces, linked through a unified hypersonic database. The graphical interfaces are capable of highlighting the key project drivers along varying levels of categorisation and refinement. Aided by these newly developed data and information support interfaces covering past and present hypersonic efforts, the planner's forecasting assessment of present and future hypersonic research and development efforts is pragmatically enriched towards a more complete managerial program-planning framework.